Communication and the Civil Sphere: Discovering Civil Society in Journalism Studies. (April 2015) - Forde, Kathy Roberts
This essay is an effort to introduce civil sphere theory to fellow communication scholars. The primary goals are to sketch its central concepts and theoretical framework, demonstrate its explanatory power through reference to a historical case study, and suggest how it can open new pathways of inquiry and understanding for those who study communication and social movements. The secondary goal is to persuade scholars of journalism studies that the concepts civil society and civil sphere have much to offer those who take seriously journalism's role in democratic struggle.